Examining the Role of Vasopressin in the Modulation of Parental and Sexual Behaviors - Zimmermann-Peruzatto, Josi Maria; Lazzari, Virgínia Meneghini; de Moura, Ana Carolina; Almeida, Silvana; Giovenardi, Márcia (Frontiers in Psychiatry, 2015)
Vasopressin (VP) and VP-like neuropeptides are evolutionarily stable peptides found in all vertebrate species. In non-mammalian vertebrates, vasotocin (VT) plays a role similar to mammalian VP, whereas mesotocin and isotocin are functionally similar to mammalian oxytocin (OT). Here, we review the involvement of VP in brain circuits, synaptic plasticity, evolution, and function, highlighting the role of VP in social behavior. In all studied species, VP is encoded on chromosome 20p13, and in mammals, VP is produced in specific hypothalamic nuclei and released by the posterior pituitary. The role of VP is mediated by the stimulation of the V1a, V1b, and V2 receptors as well as the oxytocinergic and purinergic receptors. VT and VP functions are usually related to osmotic and cardiovascular homeostasis when acting peripherally. However, these neuropeptides are also critically involved in the central modulation of social behavior displays, such as pairing recognition, pair-bonding, social memory, sexual behavior, parental care, and maternal and aggressive behavior. Evidence suggests that these effects are primarily mediated by V1a receptor in specific brain circuits that provide important information for the onset and control of social behaviors in normal and pathological conditions.